1989
DOI: 10.1080/01635588909514037
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of basic anthropometric data in children with advanced solid tumors

Abstract: In pediatric cancer patients, malnutrition is commonly observed. This may represent the metabolic effect of the primary disease or it may be a consequence of multimodal therapy. This report evaluates the efficacy of using basic anthropometric measurements to predict morbidity during therapy. Twenty children with Wilms' tumor (Stage III, IV, and V) or neuroblastoma (Stage IV) diagnosed at Children's Hospital (Columbus, OH) between January 1983 and December 1985 were evaluated. When compared with the Wilms' tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…reported that children with neuroblastoma had a significantly lower weight for age at diagnosis when compared with those of Wilms’ tumor. [ 22 ] Their weight for height and weight for age at completion were statistically lower ( P < 0.05). They spent a greater proportion of their treatment time as hospital-admitted patients and had more frequent hospital admissions, longer delays in therapy, and more complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that children with neuroblastoma had a significantly lower weight for age at diagnosis when compared with those of Wilms’ tumor. [ 22 ] Their weight for height and weight for age at completion were statistically lower ( P < 0.05). They spent a greater proportion of their treatment time as hospital-admitted patients and had more frequent hospital admissions, longer delays in therapy, and more complications.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 18 19 ] Most of them have studied the role of nutrition in neuroblastoma along with other cancers and have included few patients of neuroblastoma. [ 20 21 22 23 24 ] Thus, the impact of nutritional status on neuroblastoma was not very clear.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 20 children with advanced stage WT suggested an increase in drug toxicity for those who were lower weight-for-height [7]. Another study, conducted in South Africa, demonstrated no effect of low weight (< 3%) or low weight-for-height on the morbidity of treatment or survival in 59 children with a mixture of stages of FH WT [8].…”
Section: Introductionmentioning
confidence: 99%
“…Among patients with Wilms tumor, however, those with greater weight-loss-for-height percentiles had poor tolerance to treatment and an increased frequency of hospital admissions. 8 Objective measures of nutritional status such as albumin levels and weight loss are important clinical indicators. They provide objective evidence of anorexia/cachexia and are useful in monitoring response to treatment and prognosis.…”
mentioning
confidence: 99%